Abstracts from the 5. Australian conference on mathematics and computers in sport, 2000 (2000)
Mathematics and Computers in Sport 2000 The conference brought together sports scientists who are interested in mathematical and statistical modelling in sport, the use of computers in sport, the application of these to improve coaching and individual performance, and teaching that combines mathematics, computers and sport. Previous conferences on Mathematics and Computers in Sport have been held at Bond University, Gold Coast, Queensland, every two years since 1992. With the Olympic Games being held in Sydney in 2000, the opportunity is being taken to meet there and view the site of the Games.